ARMENIA’S PARTICIPATION IN THE GLOBALIZATION PROCESSES - VARTANIAN, Arsen (CENTRAL ASIA AND THE CAUCASUS, 2006)
Integration of the Republic of Armenia (RA) into the global trade and economic system, which began after 1991, is proving to be a far from smooth process. Its main focus is carrying out targeted reforms aimed at liberalizing trade conditions, opening up markets, and creating conditions for free competition. The steps taken have brought the country’s economy closer to the standards of the World Trade Organization (WTO) and prepared the way for the republic’s entry into this international structure. For example, a great deal of preparatory work has been done to improve the legislative base in the economy and in trade in keeping with WTO requirements. This preparatory work has been especially aimed at creating propitious conditions for equal competition, the development of small and medium enterprises, and the protection of domestic markets, as well as at encouraging anti-dumping measures. What is more, significant changes have been introduced into the Customs Code and legislation on the protection of intellectual property rights. On the whole, Armenia’s entry into the WTO has been difficult and rather painful for its transitional economy. It progressed slowly and had to surmount obstacles along the way, including those raised by certain public officials and the parliamentary opposition. Nevertheless, on 10 December, 2002, the WTO General Council in Geneva officially approved Armenia’s membership in this organization. All that remains is for the republic’s parliament to ratify the membership protocol. Thirty days after the WTO secretariat sends official notification that this procedure has been successfully concluded, the country will automatically become a full-fledged member of the World Trade Organization. The RA believes that membership in the WTO will fortify its legal framework and market mechanisms aimed at ensuring its participation in international trade. What is more, after receiving the status of most favored nation, the republic will have the best guarantee of its access to the world economic markets, which, in particular, will make it possible for it to significantly increase export to the WTO member states due to the removal of trade barriers. At the same time, the country’s investment climate will improve and the activity of foreign investors in various segments of its economy will increase. As we have already noted, the transition to integration into the world economic system has been rather agonizing for Armenia. Shock therapy, which began with a devastating earthquake (at that time 25,000 people were killed and 500,000 were affected in some way or another) and the Nagorno-Karabakh conflict, damaged the republic’s economy. The high inflation and abrupt rise in consumer prices which resulted from this put the total GDP in 1993 at no more than 50% of the same index for 1990